CPOB Sediaan Steril - Dewi Rahmawati; Dzakiya Zhihrotulwida; M. Fitrul Mubarak; Ismatun Maulidiyah; Elsa Saqila; Aprilia Puji; Ika Hepi; Silvi Novita Permatasari (Calory Journal Medical Laboratory Journal, 2024)
The importance of Good Manufacturing Practices (GMP) in the pharmaceutical industry to ensure the quality and safety of drug products. GMP aims to ensure that all pharmaceutical preparations, including sterile drugs such as infusions and injections, meet strict quality standards. Sterility testing is an important aspect even though it has limitations, such as long incubation times and low probability of detecting contamination. Therefore, any sterility test results that do not meet the requirements must be further investigated to find the cause, either from laboratory errors or contamination in the production process. In addition, the implementation of technical and managerial aspects in accordance with GMP, such as temperature and humidity control, is very important to maintain product quality. This article also highlights the use of modern technologies, such as Service Oriented Architecture (SOA), to improve efficiency and transparency in the drug production process, so that it can meet all the provisions set.